LEVEL OF JOB SATISFACTION AMONG REGISTERED NURSES WORKING IN CLINICAL AREA AT TEACHING HOSPITAL: A STUDY FROM LOCAL POPULATION - NAWAZ , R; PERVEEN , T; NAZAR , K (Biological and Clinical Sciences Research Journal, 2024)
Job satisfaction is crucial to a nurse's life, impacting patient safety, productivity, performance, quality of care, and commitment to the organization and the profession. The objective of this study was to evaluate the level of job satisfaction among registered nurses working at different local hospital of Multan, Punjab, Pakistan. The study employed a cross-sectional descriptive survey design with a sample of 102 registered nurses selected through random sampling. A self-reported questionnaire was used to collect data, and the inclusion criteria were comprised of female regular nurses registered with the Pakistan Nursing Council. Primary data was collected through semi-structured interviews, and secondary data, which consisted of 30 questions, was collected. All participants in this study were female, most of whom were aged between 26 and 30 (53.92%). Most respondents (89, 87.3%) had a diploma in general nursing, and most had working experience ranging from 6 months to 5 years (49, 48.0%). The majority of the respondents were married (58, 56.9%). Out of 102 respondents, 63 (61.77%) were satisfied, 45 (44.12%) were neutral, and 14 (13.72%) were dissatisfied. The corresponding percentage in the satisfied category (61.77%) is higher than in the remaining categories. Nurses are not entirely satisfied with their work. The level of job satisfaction among nurses varies with age, qualification, working experience, and marital status. At different local hospital of Multan., nurses are not fully satisfied with their jobs due to more patients than staff nurses, low salaries, job insecurity, lack of opportunities for promotion, and no daycare center for the duty staff's children.